Developing and Evaluating OSCE-based, Comprehensive Clinical Competency of Nursing Students, Srimahasarakham Nursing College - Numsang, Patcharee; Kumsiriruk, Natapon; Tilakarayasrup, Sujima; Thongdornbom, Suwakon; Panmuang, Sivaporn (Journal of Public Health Nursing, 2021)
Objective Structured Clinical Examination (OSCE) can help to improve clinical skills and prepare students for practice in clinical settings. This action research aimed to develop and evaluate the OSCE-based comprehensive clinical competency of nursing students at Srimahasarakham Nursing College. The participants consisted of 371 nursing students and 50 nursing instructors. The research process was conducted in four phases: 1) planning, 2) acting, 3) observing, and 4) reflecting. Instruments included an OSCE evaluation, a questionnaire to measure student satisfaction with OSCE tests, and after-action review (AAR). The study was carried out from October 2017 to December 2019. The data were analyzed using descriptive statistics and content analysis. Instructors evaluated OSCE-based, comprehensive clinical competency in real-time at 14 stations. Results indicate that knowledge and skill competencies of nursing students were good or higher (60 %) in areas including CPR (100 %), vaccine injection (92 %), normal labor (94.89 %), child growth and development (88.83 %), visual acuity test (91.24 %), and physical examination (62.69 %). The students expressed reasonable satisfaction with the OSCE evaluation ( =3.88, SD 0.47). They feel excited about the test and feel confident about caring for patients after graduation. The college should adopt this testing practice and support an OSCE comprehensive clinical competency evaluation tangibly and continuously.